ZORA 148: Narečno besedje slovenskega jezika: V spomin na akademikinjo Zinko Zorko (University of Maribor Press, 2022)
Dialectal Words of Slovene Language: In the Memory of the Academician Zinka Zorko. The monograph Dialectal Words of Slovene Language. In the Memory of the Academician Zinka Zorko presents Zinka Zorko’s work and the latest Slovene research which continue Zorko’s work in the field of dialectology in sixteen chapters: Zinka Zorko and Pleteršnik days, Zinka Zorko and Slovenian Linguistic Atlas, Dialectal Image of the Malečnik Local Speech, Germanisms of the Malečnik Local Speech, Word-Formation Characteristics of Common Personal Nouns of the Malečnik Local Speech, Fonetics Images of the Novo Mesto Speech, Traditional Professions of the Gorenjska Countryside as a Motivation for Dialect House Names, Translation and Dubbing: Theoretical and Methodological Bases and Personal Experience with Translation and Dubbing of Dialectological Films, Dialectal Vocabulary in the Ethnological Treatise of Avgus, Typology of Semantic Transfers in Slovene Dialects (with a Special Focus on Western Slovene Dialects), (Bavarian) High German and (Carnian) Friulian Elements in Resian Personal Names, Digitizing Pleteršnik’s Manuscript Collection of Geographical Names, Metelko’s 1823 Collection of Slovenian Toponyms, Project Historical Topography of Primorska region, Projects Every village has its own voice also in the Municipality of Brežice.